Ten simple rules for surviving an interdisciplinary PhD. - Demharter, S; Pearce, N; Beattie, K; Frost, I; Leem, J; Martin, A; Oppenheimer, R; Regep, C; Rukat, T; Skates, A; Trendel, N; Gavaghan, D; et al. (Public Library of Science, 2017)
Many of today's pressing research challenges require a multifaceted approach that combines several historically distinct disciplines. As a result, there has been a surge in funding for interdisciplinary PhD programmes. Some examples include the United States National Science Foundation (NSF) Research Traineeship (NRT) (succeeds the Integrative Graduate Education and Research Traineeship [IGERT]); the European Research Council's Innovative Training Network (ITN); and, in the United Kingdom, strong growth in interdisciplinary doctoral programmes across all research councils, led by the Engineering and Physical Sciences Research Council (EPSRC) and their Centres of Doctoral Training (CDTs), with the strong support of UK universities and industrial partners. First and foremost, an interdisciplinary PhD is a great chance for students to pursue truly novel research, a range of different career paths, and a stimulating intellectual life. However, these benefits are often accompanied by additional academic and logistical challenges. The rules presented here aim to provide guidelines that will enable PhD candidates to maximise the benefits of interdisciplinary research whilst minimising any burdens.